Assessing the incremental benefit of an extended duration lifestyle intervention for the components of the metabolic syndrome - Walden P (Dove Medical Press, 2016)
Patrick Walden, Qingmei Jiang, Elizabeth A Jackson, Elif A Oral, Martha S Weintraub, Melvyn Rubenfire Division of Cardiovascular Medicine, Cardiovascular Medicine at Domino’s Farms, University of Michigan Health System, Ann Arbor, MI, USA Background: Lifestyle interventions targeting the components of the metabolic syndrome (MetSyn) have been demonstrated to be a cost-effective and suitable treatment strategy for reducing one’s risk of developing coronary artery disease and diabetes. The optimal duration has not yet been defined. We sought to evaluate the incremental benefit of extending a lifestyle intervention from 3 months to 6 months. Methods: We evaluated 114 participants with at least three criteria for the MetSyn in a physician-referred 6-month lifestyle intervention between August 2008 and December 2012. Baseline and follow-up physiological, biochemical, and anthropometric data were analyzed for mean change and incremental change at each time point. Results: The mean age at enrollment was 53.0±10.2 years, and 42% of participants were males. The mean body mass index at enrollment was 38.2±0.86 kg/m2 for males and 38.6±0.93 kg/m2 for females. Anthropometric measures associated with weight management (body mass index, weight, and body fat percentage) improved significantly with the additional 3-month intervention (P<0.001). Systolic blood pressure (P=0.0001) and diastolic blood pressure (P=0.00006) and triglycerides, fasting blood glucose, and homeostatic model assessment of insulin resistance in diabetic participants (P=0.006, P=0.004, P=0.01, respectively) improved rapidly in the initial 3-month intervention without incremental benefit of the additional 3 months. Improvements in fasting insulin (P=0.01) and homeostatic model assessment of insulin resistance (P=0.02) for nondiabetic participants required the full 6-month intervention before significant reductions were achieved. Conclusion: A 6-month lifestyle intervention yielded significantly better results for variables related to weight management. Standard physiological measures for the MetSyn respond rapidly in a 3-month lifestyle intervention. The long-term impact of an increased duration lifestyle intervention remains to be seen. Keywords: lifestyle intervention, metabolic syndrome, diabetes